Regional and global large-scale dynamics associated with a prolonged drought event in Greece - Prezerakos, N.G.a; Flocas, H.A.b (Journal of Atmospheric and Solar-Terrestrial Physics, 2002)
The large-scale dynamical processes associated with an exceptionally dry and warm autumn during 1993 in Greece were studied. On the regional scale, it was found that low-frequency eddies prevailed over Europe in the form of a block with large-scale descending motion persisting throughout the whole troposphere. Moreover, the subtropical jet was unusually positioned much farther north over the Balkan peninsula and oscillated between this position and one over the central mainland of Greece where it interacted with the southern part of the polar front jet. On the global scale, it was found that this type of atmospheric circulation over Europe was closely related with a region of latent heat release in convective clouds over the tropics between the longitudes 100° and 120°E, and the formation of a steady divergence system at 150 hPa over the same region, strongly affecting the global rotational flow. © 2002 Elsevier Science Ltd. All rights reserved.
cited By (since 1996)1
Keywords: atmospheric dynamics; Drought; eddy; Greece; Rossby wave